Narrativas relacionadas con las experiencias sociales, familiares y emocionales de un grupo de personas mayores de 60 años o más a partir del uso de las TIC (2024)
As the main basis of this research work, it was established to analyze the narratives related to the social, family and emotional experiences of a group of four people over 60 years of age, based on the use of ICT, managing to identify through them, a series of experiences from which the participants revealed what the process of interaction and adaptation with ICT has been like, and how these factors have influenced their different areas of adaptation. Aspects such as the emotional experiences within the narratives of older adults based on the use of ICT were investigated, with the emotion of happiness generally manifested among the participants, this as a consequence of the interactions that they have been able to establish and maintain at the moment. at the family level, and how these have transcended social spheres, which has allowed them to adapt and be an active and participatory part of their environment.